Poverty Analysis of 13 Districts/Cities in Central Sulawesi Province - Tinadji, Selvika; Taqwa, Edhi; Lutfi, Muhtar; Yohan, Yohan; Sading, Yunus; Armin, Armin (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2025)
Indonesia is still grappling with considerable poverty issues, as more than 24 million individuals are currently living below the poverty line. Central Sulawesi Province is ranked as the 15th highest in terms of poverty levels across the nation, with almost 380,000 of its residents considered impoverished. From 2019 to 2023, this province's poverty rate has demonstrated varying patterns, hovering between 12% and 13%. In response to these conditions, this study seeks to examine how the average duration of schooling, level of open unemployment, and Regional Domestic Product (RDP) impact poverty rates in 13 districts and cities in the Central Sulawesi Province over the period 2020 to 2024. This research adopts a quantitative method using data sourced from the Central Statistics Agency (BPS) of Central Sulawesi. The analysis was carried out through panel data regression using Eviews 12 software. Findings from the research show that, individually, both the open unemployment rate and average duration of schooling have a significant impact on poverty levels, while the growth rate of RDP does not. Collectively, all three independent variables are influential on poverty in the 13 districts and cities of Central Sulawesi Province from 2020 to 2024. These findings highlight the urgency for focused policy measures to tackle poverty in Central Sulawesi Province, with particular emphasis on reducing unemployment and improving the quality of education.